2016
DOI: 10.1073/pnas.1608045113
|View full text |Cite
|
Sign up to set email alerts
|

Holdase activity of secreted Hsp70 masks amyloid-β42 neurotoxicity in Drosophila

Abstract: Alzheimer’s disease (AD) is the most prevalent of a large group of related proteinopathies for which there is currently no cure. Here, we used Drosophila to explore a strategy to block Aβ42 neurotoxicity through engineering of the Heat shock protein 70 (Hsp70), a chaperone that has demonstrated neuroprotective activity against several intracellular amyloids. To target its protective activity against extracellular Aβ42, we added a signal peptide to Hsp70. This secreted form of Hsp70 (secHsp70) suppresses Aβ42 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 60 publications
2
54
0
Order By: Relevance
“…The pre-incubation of these aggregates with clusterin also reverted their ability to reduce the pharyngeal mobility in C. elegans nematodes (Beeg et al, 2016). In another study, Hsp70 was modified to be released in the extracellular space in order to address its protective activity against Aβ 42 in Drosophila melanogaster models (Fernandez-Funez et al, 2016). The secreted form, called secHsp70, suppressed Aβ 42 toxicity, as deduced by decreased eye degeneration, reduced neuronal death, structural integrity of adult neurons, suppression of locomotor neuron dysfunction, and lifespan extension.…”
Section: Chaperones Shield the Hydrophobic Moieties Of The Oligomers mentioning
confidence: 99%
See 2 more Smart Citations
“…The pre-incubation of these aggregates with clusterin also reverted their ability to reduce the pharyngeal mobility in C. elegans nematodes (Beeg et al, 2016). In another study, Hsp70 was modified to be released in the extracellular space in order to address its protective activity against Aβ 42 in Drosophila melanogaster models (Fernandez-Funez et al, 2016). The secreted form, called secHsp70, suppressed Aβ 42 toxicity, as deduced by decreased eye degeneration, reduced neuronal death, structural integrity of adult neurons, suppression of locomotor neuron dysfunction, and lifespan extension.…”
Section: Chaperones Shield the Hydrophobic Moieties Of The Oligomers mentioning
confidence: 99%
“…The secreted form, called secHsp70, suppressed Aβ 42 toxicity, as deduced by decreased eye degeneration, reduced neuronal death, structural integrity of adult neurons, suppression of locomotor neuron dysfunction, and lifespan extension. An assay based on luciferase-derived luminescence showed that secHsp70 stabilizes Aβ 42 oligomeric species and masks their neurotoxic epitopes, thus promoting the accumulation of nontoxic aggregates (Fernandez-Funez et al, 2016). This activity was carried out in the absence of ATP, indicating therefore that secHsp70 exploits its holdase function to interact with the oligomers in the absence of detectable clustering (Fernandez-Funez et al, 2016).…”
Section: Chaperones Shield the Hydrophobic Moieties Of The Oligomers mentioning
confidence: 99%
See 1 more Smart Citation
“…Hsp70 variants with enhanced chaperone or disaggregase activity against specific model substrates have been uncovered [9497], but whether these can be translated into neuroprotective agents in vivo is unknown. Engineering a secreted form of Hsp70 rescued a Drosophila model of AD, although in this case Hsp70 promoted clustering of Aβ42 into larger aggregates with reduced neurotoxicity [98•]. This clustering activity appears to be a general feature of molecular chaperones that must operate under ATP-limited conditions such as the extracellular space, and can be protective by minimizing exposure of reactive surfaces by confining them within the aggregate interior [43••,99].…”
Section: Hsp110 Hsp70 and Hsp40 Disaggregases In Humansmentioning
confidence: 99%
“…Each ommatidium consists of eight photoreceptor neurons, which project axons that synapse in the optic ganglia of the brain [254]. The defined structure of the ommatidia can be disrupted by, for example, the expression of toxic proteins or genetic alterations, resulting in a rough eye phenotype easily detected by light microscopy or scanning electron microscopy [255]. A frequently used tool to study eye specific expression is the GMR-Gal4 driver.…”
Section: Rna Binding Protein Expressed In Neurons That Is Necessarymentioning
confidence: 99%